Nonomuraea corallina sp. nov., isolated from coastal sediment in Samila Beach, Thailand: insights into secondary metabolite synthesis as anticancer potential - Ngamcharungchit, Chananan; Matsumoto, Atsuko; Suriyachadkun, Chanwit; Panbangred, Watanalai; Inahashi, Yuki; Intra, Bungonsiri (Frontiers in Microbiology, 2023)
A novel marine actinomycete, designated strain MCN248 T , was isolated from coastal sediment in Songkhla province, Thailand. Based on 16S rRNA gene sequences, the new isolate was most closely related to Nonomuraea harbinensis DSM45887 T (99.2%) and Nonomuraea ferruginea DSM43553 T (98.6%). Phylogenetic analyses based on the 16S rRNA showed that strain MCN248 T was clustered with Nonomuraea harbinensis DSM45887 T and Nonomuraea ferruginea DSM43553 T . However, the digital DNA-DNA hybridization analyses presented a low relatedness of 40.2% between strain MCN248 T and the above closely related strains. This strain contained mesodiaminopimelic acid. The acyl type of the peptidoglycan was acetyl, while mycolic acids were absent. The major menaquinones were MK-9(H2) and MK-9(H4). The whole-cell sugars consisted of madurose, ribose, mannose and glucose. Diphosphatidylglycerol, hydroxylphosphatidylethanolamine, phosphatidylethanolamine, phosphatidylinositol and phosphatidylglycerol were detected as the major phospholipids. The predominant cellular fatty acids were iso-C16:0 (40.4%), 10-methyl-C17:0 (22.1%) and C17:1ω8c (10.9%). The DNA G+C content of the genomic DNA was 71.7%. With in silico analyses, antiSMASH platform uncovered a diverse twenty-nine secondary metabolite biosynthesis arsenal, including non-ribosomal peptide synthetase (NRPS), and polyketide synthase (PKS) of strain MCN248 T , with high prevalence of gene clusters encoding pathways for the production of anticancer, and cytotoxic compounds.Consistently, the crude extract could inhibit colorectal HCT-116 cancer cells at final concentration of 50 g/mL. Based on the polyphasic approach, strain MCN248 was designated as a novel species of the genus Nonomuraea, for which the name Nonomuraea corallina sp. nov. is proposed. The type strain of the type species is MCN248 T (=NBRC115966 T =TBRC17110 T ).